Caring Leadership: A Heideggerian Perspective. Issue 8 (August 2015) - Tomkins, Leah; Simpson, Peter
This paper develops the idea of caring leadership based on Heidegger's philosophy of care. From this perspective, caring leadership is grounded in the practices of 'leaping-in' and 'leaping-ahead' as modes of intervention in the affairs of the world and the efforts of others. This involves gauging and taking responsibility for the ramifications of intervention, balancing the urge for certainty of outcome and visibility of contribution with the desire to encourage and enable others. Our analysis suggests several twists to contemporary leadership debates. We argue that the popular models of transactional and transformational leadership are to be critiqued not for their over-reliance but, rather, their under-reliance on agency. This is a different kind of agency to that of heroic or charismatic models. It involves tolerance of complexity and ambivalence; a rich sense of temporal trajectory; concern for one's presence in the world; and crucially, the ability to resist the soothing normativity of 'best practice'. From this position, we argue that the problem with the growing scholarly interest in an ethic of care is that it provides too tempting a recipe to follow. In a Heideggerian view, caring leadership has little to do with compassion, kindness or niceness; it involves and requires a fundamental organization and leadership of self.